2012
DOI: 10.1136/amiajnl-2012-000823
|View full text |Cite
|
Sign up to set email alerts
|

Data quality assessment in healthcare: a 365-day chart review of inpatients' health records at a Nigerian tertiary hospital

Abstract: Inadequacies were found in clinical documentation, especially gross underutilization of discharge summary forms. However, some forms were properly documented, suggesting that hospital healthcare providers possess the necessary skills for quality clinical documentation but lack the will. There is a need to institute a clinical documentation improvement program and promote quality clinical documentation among staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 11 publications
(12 reference statements)
1
48
0
Order By: Relevance
“…On the other hand, it is evident from our study that clinical coding practices and especially, implementation of ICD-10 and its procedure counterpart, ICD-10-PCS is no longer a mirage in Nigeria as 88% of healthcare settings in Nigeria practice full diagnoses coding with ICD-10 and 39% carry out procedure coding using ICD-10-PCS. This further supports a study [11] from Nigeria that most (81%) of the discharged patients' folders reviewed in the study were coded. The preponderance of paper-based health records systems [31][32] has multiplying effects on the practice of clinical coding seeing that as low as 7% operate automated coding.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…On the other hand, it is evident from our study that clinical coding practices and especially, implementation of ICD-10 and its procedure counterpart, ICD-10-PCS is no longer a mirage in Nigeria as 88% of healthcare settings in Nigeria practice full diagnoses coding with ICD-10 and 39% carry out procedure coding using ICD-10-PCS. This further supports a study [11] from Nigeria that most (81%) of the discharged patients' folders reviewed in the study were coded. The preponderance of paper-based health records systems [31][32] has multiplying effects on the practice of clinical coding seeing that as low as 7% operate automated coding.…”
Section: Discussionsupporting
confidence: 72%
“…Cunningham et al [43] also reported insufficient information for specific code assignment. Similarly, documentation issues have been of primary concern for coding quality [44] and it has been suboptimal in developing nations such as Nigeria [11] where discharge summary is reported to be grossly underutilized. Bad clinical documentation makes information inaccessible [45] and causes coding errors [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of this, the global relevance and importance of computer and the Internet for communication, information retrieval and support for healthcare service delivery, training and research cannot be overstated. In the same vein, accurate, promptly documented and regularly reviewed healthcare information is essential to healthcare delivery system [17]. This may not be possibly achieved without the use of computer and the Internet in processing healthcare information especially, in this hi-tech age [16].…”
Section: Introductionmentioning
confidence: 99%
“…Although the results have generally shown that most of the items checked on nursing records in the UTI-P are adequate in relation to safety aspects, it is believed that improvements can still be made through continuing education programs made available to nursing professionals (14,15) . It has been noted that in health care…”
Section: Discussionmentioning
confidence: 99%